2012
DOI: 10.2111/rem-d-11-00133.1
|View full text |Cite
|
Sign up to set email alerts
|

Stocking Rate and Riparian Vegetation Effects on Physical Characteristics of Riparian Zones of Midwestern Pastures

Abstract: Grazing at high stocking rates May Increase sediment and nutrient loading of streams pasture Through Transport in precipitation runoff and bank erosion. A 3-yr (2007)(2008)(2009)) grazing study was Conducted on 13 cool-season grass pastures to quantify effects of stocking rate and botanical composition on forage sward height, proportions of bare and manure-covered ground, and bank erosion adjacent to streams. Pastures ranged from 2 ha to 107 ha with stream Reaches of 306 m to 1778 m That has drained watersheds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Of interest, total P (Crosland et al 1995) in the soils ranged from 267 to 349 mg kg , which is comparable to total P (TP) measured in other Iowa watersheds with similar soil types (Zaimes et al 2008;Nellesen et al 2011). Additional information describing the 13 study sites is available from Bear et al (2012) and Tufekcioglu et al (2012).…”
Section: Watershed Characteristicsmentioning
confidence: 64%
See 1 more Smart Citation
“…Of interest, total P (Crosland et al 1995) in the soils ranged from 267 to 349 mg kg , which is comparable to total P (TP) measured in other Iowa watersheds with similar soil types (Zaimes et al 2008;Nellesen et al 2011). Additional information describing the 13 study sites is available from Bear et al (2012) and Tufekcioglu et al (2012).…”
Section: Watershed Characteristicsmentioning
confidence: 64%
“…Site selection was based on landowner permission to access a site during the study and perennial flow in all pasture stream reaches. When the study of Bear et al (2012) was initiated, surface horizons (0-20 cm) of soils at each site were sampled to determine inherent soil properties. Of interest, total P (Crosland et al 1995) in the soils ranged from 267 to 349 mg kg , which is comparable to total P (TP) measured in other Iowa watersheds with similar soil types (Zaimes et al 2008;Nellesen et al 2011).…”
Section: Watershed Characteristicsmentioning
confidence: 99%
“…, 2005). A study conducted by Bear et al. (2012) found that reducing the stocking rate and altering the distribution of cattle will reduce the risk of nutrient loss to surface runoff from riparian areas of grazed pastures.…”
Section: Discussionmentioning
confidence: 99%
“…In a three‐year study, Bear et al . () did not find significant differences in bare ground coverage nor bank erosion between high and low intensity grazing in riparian zones. Meanwhile, other studies have shown significant increases in bare ground coverage with increasing grazing pressures (Russell et al ., ; Zhao et al ., ), and in some instances cattle have been shown to increase bare ground quite rapidly (over 10% within two years) (Hillhouse et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation cover is the most influential variable in determining aquatic sediment and nutrient loading from adjacent hillslopes (Haan et al, 2006). Vegetation decreases wind and runoff erosion by limiting the area of exposed soils (Li et al, 2007;Bastin et al, 2012), entrapping mobilized soil particles, increasing soil stability, infiltration rates, and litter cover, while decreasing rain splash impact (Pearce et al, 1998;Bear et al, 2012). Many studies indicate that cattle grazing decreases grass biomass, resulting in bare ground (Popolizio et al, 1994;Kutt and Woinarski, 2007;Teague et al, 2010), leading to accelerated soil erosion and increased fluvial suspended sediment concentrations (Olley and Wasson, 2003;Vidon et al, 2008;Bartley et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%